2011
DOI: 10.1021/ja201844c
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Highly Reactive Dienophiles for the Tetrazine–trans-Cyclooctene Ligation

Abstract: Computation was used to design a trans-cyclooctene derivative that displays enhanced reactivity in the tetrazine-trans-cycloctene ligation. The optimized derivative is a (E)-bicyclo[6.1.0]non-4-ene with a cis-ring fusion, in which the eight-membered ring is forced to adopt a highly strained ‘half-chair’ conformation. Toward 3,6-dipyridyl-s-tetrazine in MeOH at 25 °C, the strained derivative is 19 and 27 times more reactive than the parent trans-cyclooctene and 4E-cyclooct-4-enol, respectively. Toward 3,6-diphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
349
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(365 citation statements)
references
References 51 publications
14
349
0
2
Order By: Relevance
“…4b). Inspired by the work of Dommerholt et al 96 , it was found that trans-bicyclononene reacted at yet faster rates (while noting the caveats on rate determinations given above) 103 . In addition to allowing labelling of highly dynamic processes, such rapid and efficient reactions allow the concentrations of reactive partners to be lowered significantly, reducing background labelling particularly in cases where it is REVIEW implausible to wash away excess reagent, such as intracellularly or in animal models 104 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…4b). Inspired by the work of Dommerholt et al 96 , it was found that trans-bicyclononene reacted at yet faster rates (while noting the caveats on rate determinations given above) 103 . In addition to allowing labelling of highly dynamic processes, such rapid and efficient reactions allow the concentrations of reactive partners to be lowered significantly, reducing background labelling particularly in cases where it is REVIEW implausible to wash away excess reagent, such as intracellularly or in animal models 104 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…This process was reported to take place via aminal formation as confirmed by 1 H-NMR. 13 Concise information on isomerisation from 3 to 4 as well as on the final oxidation step in terms of a systematic study is still missing. This may be the case due to two reasons: firstly, the initial [4+2] cycloaddition was identified to be the rate determining step and thus further reaction steps were neglected.…”
Section: Mechanismmentioning
confidence: 99%
“…However, many of these derivatives have low water solubility, require complex multistep synthesis, and possess suboptimal kinetics. Our search for alternative rapid, selective, and chemically accessible coupling reactions without need for a catalyst led us and others to investigate the [4 þ 2] inverse Diels-Alder cycloaddition (10)(11)(12)(13). We realized that this set of chemistries is more uniquely suited to biological applications and may indeed represent a universal platform technology ( Fig.…”
mentioning
confidence: 99%